What is difference? Deleuze and Saint Thomas - Teschke, Henning (Verbum – Analecta Neolatina, 2004)
The difference between the univocal and the equivocal concept of being marks a firm separation of philosophy from theology. Considering the analogia entis as the core structure of the epistemology of Thomas corresponding to the concept of being as the supreme reference point of his metaphysics, Deleuze misses a positive concept of difference in Thomas, who cannot avoid explaining difference in relation to an external reference or to a transcendent principle. Analogical Being, whenever related to particular beings, can never say what constitutes their individuality. Therefore, Deleuze traces the tradition of ontological univocity, noting it first in Duns Scotus, in order to think about difference in a new way. Only a univocal, anti-hierarchical ontology of immanence is capable of thinking about difference in itself or of providing difference with its own concept.